1996
DOI: 10.3109/00016349609033327
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Hepatitis: a Rare Complication Associated with the use of Ritodrine During Pregnancy

Abstract: Elevation of liver enzymes is a rare complication of ritodrine. Discontinuation of therapy does not appear to be indicated as long as other signs of liver dysfunction are not present and tocolytic treatment is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…There are several publications describing the association between ritodrine and acute liver injury. One prospective study reported that ritodrine was rarely associated with liver function impairment, even when intravenous ritodrine was administered in 128 pregnant women [ 27 ]. In that study, the incidence of acute liver injury in singleton and multiple pregnancies was approximately 1.9% and 9.1%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…There are several publications describing the association between ritodrine and acute liver injury. One prospective study reported that ritodrine was rarely associated with liver function impairment, even when intravenous ritodrine was administered in 128 pregnant women [ 27 ]. In that study, the incidence of acute liver injury in singleton and multiple pregnancies was approximately 1.9% and 9.1%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…There are several publications describing the association between ritodrine and acute liver injury. One prospective study reported that ritodrine was rarely associated with liver function impairment, even when intravenous ritodrine was administered in 128 pregnant women [25]. In that study, the incidence of acute liver injury in singleton and multiple pregnancies was approximately 1.9% and 9.1%, respectively.…”
Section: Ritodrine-induced Acute Liver Injurymentioning
confidence: 95%